WATER QUALITY AND RECHARGE OF „BOŠNJACI“ SPRING (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
This paper describes the relief characteristics, climate research of the karst spring "Bošnjaci". The method of recharge the spring is described. Data on the physico-chemical quality of water and bacteriological findings at the time of research of springs, pollutants as well as their origin, zones and measures to protect the site are provided. Finally, recommendations for spring protection are given.